Building Indonesian Food Security A Review And Suggestions - Endah Sri Redjeki (INNOVATION RESEARCH JOURNAL, 2020)
Availability, access, utilization, and stability access are the central canal between economic distresses and food security. Food security in pandemic era should sort out with conservation, seed banks, building water reservoir, urban farming, and those programs involved the Penta helix to speed gaining the goals. The Government, private sectors, institutions, local community, and social entrepreneurs have to work all together to succeed in food security.